Development of Student Worksheets (LKPD) PJOK Pencak Silat Based on Qr-Code - Bachtiar, Bachtiar; Nuraeni, Hilda; Saleh, Muhammad (Journal Coaching Education Sports, 2023)
The lack of teaching materials for Pencak Silat and several movements in the Physical Education, Sports, and Health (PJOK) textbook is needed by teachers. This research aims to produce a Student Worksheet (LKPD) for PJOK Pencak Silat based on QR codes for 7th-grade students and assist PJOK teachers in facilitating PJOK learning, specifically in Pencak Silat. The method used in this research is Research and Development, using the Borg and Gall method. The subjects of this study were 7th-grade students in junior high school. The research instruments used were media assessment, material assessment, and teacher assessment. Based on the results of the assessment of the QR code-based LKPD for PJOK Pencak Silat by media experts, subject experts, and PJOK teachers, it obtained feasibility values of 89.3%, 80%, and 83.3% with the criteria of Very Feasible, Feasible, and Very Feasible, with an average assessment of 84.2%. Based on the description, it can be concluded that the QR code-based LKPD for PJOK Pencak Silat developed by the researchers is highly feasible to use. The researcher also tested the reliability of the Pencak Silat LKPD instrument using the K-R 20 formula and obtained a result of r11 0.864, which is greater than the r-table value of 0.234. This research resulted in a QR code-based LKPD for PJOK Pencak Silat that is suitable for use and can help PJOK teachers facilitate PJOK learning, particularly in the Pencak Silat subject.